Strategies for Serving Deaf-Blind Clients Institute on Rehabilitation Issues (11th, San Antonio, Texas, June 1984). - Arkansas Univ., Fayetteville. Rehabilitation Research and Training Center; Arkansas Univ., Fayetteville. Rehabilitation Research and Training Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
The publication is intended to dispel misconceptions about the vocational rehabilitation service needs of deaf-blind persons. The first of five sections presents a history and comments on the philosophy of working with deaf-blind persons. Five programmatic definitions of deaf-blindness are offered. Section 2 addresses communication modes, aids, and devices (such as specific alphabets and braille hand speech) used by this population. The third section examines five topics: (1) administrative issues (legal aspects, program management); (2) a continuum of services (multi-agency collaborative networks, models of interagency agreements); (3) special needs of deaf blind persons (broken down into categories of types of deaf-blindness); (4) counselor concerns (caseload management, orientation and mobility, housing); and (5) the vocational rehabilitation process (training, job development). Section four examines training programs to enable rehabilitation personnel to deal with deaf blind clients and provides a list of resources that can be contacted for assistance. The final section is composed of references and a list of study group members who developed the document. (CL)
Availability: Arkansas Rehabilitation Research and Training Center, Publications Dept., P.O. Box 1358, Hot Springs, AR 71902 ($6.00).
Sponsoring Agency: National Inst. of Handicapped Research (ED), Washington, DC.
Contract Number: G0083C0010/02.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Counseling Techniques; Deaf Blind; Definitions; Educational Philosophy; History; Program Administration; Psychological Needs; Vocational Rehabilitation; Guides, Non-Classroom.